2005
DOI: 10.1063/1.1883335
|View full text |Cite
|
Sign up to set email alerts
|

Deformation twinning during nanoindentation of nanocrystalline Ta

Abstract: The deformation mechanism of body-centered cubic (bcc) nanocrystalline tantalum with grain sizes of 10–30 nm is investigated by nanoindentation, scanning electron microscopy and high-resolution transmission electron microscopy. In a deviation from molecular dynamics simulations and existing experimental observations on other bcc nanocrystalline metals, the plastic deformation of nanocrystalline Ta during nanoindentation is controlled by deformation twinning. The observation of multiple twin intersections sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
59
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 22 publications
6
59
0
Order By: Relevance
“…With the help of Eqs. (19)- (21) in Section 4.2, which describe the dislocation reactions of Da, the aD reactions for transmission across the twin boundary can be described by:…”
Section: Leading 90°partial Ad Transmits Across the Twin Boundarymentioning
confidence: 99%
See 1 more Smart Citation
“…With the help of Eqs. (19)- (21) in Section 4.2, which describe the dislocation reactions of Da, the aD reactions for transmission across the twin boundary can be described by:…”
Section: Leading 90°partial Ad Transmits Across the Twin Boundarymentioning
confidence: 99%
“…Since deformation twinning usually occurs simultaneously with the slip of perfect and partial dislocations, interactions between twins and gliding dislocations inevitably occur at twin boundaries. Nanocrystalline fcc metals have been found to deform via twinning more readily than their coarse grained counterparts [11][12][13][14][15][16][17][18][19][20][21][22]. This increases the probability of interactions between dislocations and twins in nanocrystalline fcc metals.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical properties of nanocrystalline ͑nc͒ materials are controlled by their deformation mechanisms, 1 which include partial dislocation emission from grain boundaries ͑GBs͒, 2-10 deformation twinning, [9][10][11][12][13][14][15][16][17][18][19][20] full dislocations, 3,5,7 GB sliding, 3,11-13 and grain rotation. 11,14 Basing on generalized planar fault energy ͑GPFE͒ curves, molecular dynamics ͑MD͒ simulations predicted that nc Ni prefers to deform by extended partials, rather than twinning.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Deformation twins and stacking faults, indicating the presence of dislocation activities in nc grains and especially the operation of partial dislocation mediated processes, were observed in Al, [1][2][3] Cu, 4 Pd, 5,6 and Ta. 7 The nc-Al and nc-Pd cases are especially interesting, as these fcc metals have high stacking fault energies and little or no chance of undergoing deformation twinning in their coarse-grained form ͑conventional fcc Cu, in comparison, is known to twin when deformed at low temperatures and/or high strain rates͒. However, there appears to be a glaring contradicting example: recent in situ x-ray diffraction studies of fcc nc-Ni subjected to tensile deformation showed no irreversible peak broadening.…”
mentioning
confidence: 99%